Leveraging Procedural Reforms to Improve Commercial Justice in Bosnia and Herzegovina - World Bank (World Bank, Washington, DC, 2019)
This report focuses on recommendations for the improvement of civil procedure rules and selected trial processes with the aim to increase procedural efficiency and reduce bottlenecks in commercial case processing in Bosnia and Herzegovina. The following aspects of case processing are analyzed: (i) service of process; (ii) hearings and adjournments; (iii) expert witnesses; (iv) bankruptcy trustees; (v) court fees; (vi) internal court rules; and (vii) use of Case Management System (CMS). The accompanying recommendations are developed in response to the existing legal framework that governs these selected aspects of commercial case processing and rely on existing good examples from Bosnia and Herzegovina courts, the regulatory framework of countries that share the same legal heritage as Bosnia and Herzegovina with a particular focus on European Union and Council of Europe member states, the European Court of Human Rights (ECtHR) case law, as well as recommendations and opinions of international institutions on judicial efficiency.